Estimación de la curva de rendimiento cupón cero para el Perú y su uso para el análisis monetario - Pereda C., Javier (2010)
This paper estimates the zero coupon yield curve for the Peruvian government bond market. We employ two methods of estimation proposed by Nelson y Siegel (1987) and Svensson (1994). Model performance is evaluated based on criteria of goodness of fit, flexibility and parameter stability, by using alternative objective functions for parameter estimation. The Svensson model shows on average a better adjustment; however, parameter estimates are more unstable when data availability is limited —for example when there is a small number of transactions in the secondary market— in which case is better to use the Nelson y Siegel estimates. At the end of the paper, yield curve estimates are used to derive market expectations of future short term interest rates, that are valuable sources of information for central bank’s monetary policy.